DNA aerogels and DNA-wrapped CNT aerogels for neuromorphic applications. (December 2022) - Hosseini, Mahshid; Rahmanian, Vahid; Pirzada, Tahira; Frick, Nikolay; Krissanaprasit, Abhichart; Khan, Saad A.; LaBean, Thomas H.
Abstract: Nucleic acids are programmable materials that can self-assemble into defined or stochastic three-dimensional network architectures. Various attributes of self-assembled, cross-linked Deoxyribonucleic acid (DNA) hydrogels have recently been investigated, including their mechanical properties and potential biomedical functions. Herein, for the first time, we describe the successful construction of pure DNA aerogels and DNA-wrapped carbon nanotube (CNT) composite (DNA-CNT) aerogels via a single-step freeze-drying of the respective hydrogels. These aerogels reveal highly porous and randomly branched structures with low density. The electrical properties of pure DNA aerogel mimic that of a simple capacitor; in contrast, the DNA-CNT aerogel displays a fascinating resistive switching behavior in response to an applied bias voltage sweep reminiscent of a volatile memristor. We believe these novel aerogels can serve as a platform for developing complex biomimetic devices for a wide range of applications, including real-time computation, neuromorphic computing, biochemical sensing, and biodegradable functional implants. More importantly, insight obtained here on self-assembling DNA to create aerogels will pave the way to construct novel aerogel-based material platforms from DNA coated or wrapped functional entities. Graphical abstract: Image 1